Variability of the Lithic Raw Material in the Upper and Late Palaeolithic sites in Southeastern Poland - Dariusz Bobak (Archaeologia Polona, 2018)
In terms of supply of good quality raw materials for stone tool manufacture, the area of southeastern Poland is rather poor. Considering research conducted so far, there are only few sites that can be the basis for analysis. Nevertheless, certain phenomena seem to be characteristic on sites in southeastern Poland in the later phase of the Upper Palaeolithic and in the Late Palaeolithic. There are usually more than one kind of raw material present. Apart from local erratic flint, imported Świeciechów (grey white-spotted) and ‘chocolate’ flint dominate. The presence of both Jurassic (areas near Cracow) and Volhynian flints are poorly recorded, whereas resources from the south are almost absent. These imported raw materials indicate the existence of particularly strong relations linking the areas of southeastern Poland with the Sandomierz Upland, and much weaker relationships with the territories of Lesser Poland and Western Ukraine